Interferon-inducible SAMHD1 restricts viral replication through downregulation of lipid synthesis - An, Ni; Ge, Qinghua; Shao, Huihan; Li, Quanjie; Guo, Fei; Liang, Chen; Li, Xiaoyu; Yi, Dongrong; Yang, Long; Cen, Shan (Frontiers in Immunology, 2022)
Type I interferon (IFN) inhibits virus infection through multiple processes. Recent evidence indicates that antiviral mechanism is supported by an IFN-induced readjustment of the cellular metabolism. The sterile alpha motif and histidine-aspartate domain containing protein 1 (SAMHD1), as an interferon-stimulated gene (ISG), has been reported to inhibit a number of retroviruses and DNA viruses, by depleting the pool of dNTPs necessary for viral DNA synthesis. Here we report a new antiviral activity of SAMHD1 against RNA viruses including HCV and some other flaviviruses infection. Our data show that SAMHD1 down-regulates the expression of genes related to lipid bio-metabolic pathway, accompanied with impaired lipid droplets (LDs) formation, two events important for flaviviruses infection. Mechanic study reveals that SAMHD1 mainly targets on HCV RNA replication, resulting in a broad inhibitory effect on the infectivity of flaviviruses. The C-terminal domain of SAMHD1 is showed to determine its antiviral function, which is regulated by the phosphorylation of T592. Restored lipid level by overexpression of SREBP1 or supplement with LDs counteracts with the antiviral activity of SAMHD1, providing evidence supporting the role of SAMHD1-mediated down-regulation of lipid synthesis in its function to inhibit viral infection. Collectively, these data suggest a important role of SAMHD1 in IFN-mediated inhibition of flaviviruses infection through targeting lipid bio-metabolic pathway.